2007
DOI: 10.1097/aco.0b013e3282f172bd
|View full text |Cite
|
Sign up to set email alerts
|

The perioperative librarian: luxury or necessity?

Abstract: Anesthesiologists have particular information needs for which the physical library is no longer sufficient. New outcome measures to define the 'success' of clinical medical librarian programs need to be formulated, and economic considerations need to be factored into these programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…For example, a partnership between ‘a CNS, a health science librarian, and a staff nurse’ resulted in a carefully designed evidence‐based practice instructional programme targeting nursing staff; the CNS provided the actual transition of research into the nursing practice, while the librarian offered expertise in information retrieval . Another study noted the benefit librarians could have in assisting anaesthesiologists in answering clinical point of need questions with EBM research . Public health‐prepared librarians have served the EBM informational needs of public health professionals .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a partnership between ‘a CNS, a health science librarian, and a staff nurse’ resulted in a carefully designed evidence‐based practice instructional programme targeting nursing staff; the CNS provided the actual transition of research into the nursing practice, while the librarian offered expertise in information retrieval . Another study noted the benefit librarians could have in assisting anaesthesiologists in answering clinical point of need questions with EBM research . Public health‐prepared librarians have served the EBM informational needs of public health professionals .…”
Section: Discussionmentioning
confidence: 99%
“…More research would be necessary to establish the online tools that would be most appropriate for the ICPs' use. In the literature, several ways for librarians to provide optimal information services to perioperative staff were noted: assisting clinicians in locating answers to clinical queries via evidence‐based literature and developing websites that addressed perioperative staff needs as well as educating clinicians on search techniques for really simple syndication feeds and e‐mail alerts for receiving updates on the most recent articles . Similarly, librarians could work towards structuring various online tools appropriate for ICPs' use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Booth 11 reported that there was a low evidence base for the specialist searcher role of librarians and that it was difficult to assess the success of database searches, without a gold standard for comparison 77 . Librarians performed well against content experts when assessed in studies, 78,79 and user satisfaction studies have yielded positive results 14,75,80,81 . Others have reported gaps in expert searching knowledge and skills 23,82,83 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, to have an area of professional practice without objective measures calls into question the profession’s credibility 10,11 . Third, some health librarians have specialised roles based on expert searching such as supporting systematic reviews or clinical question answering services 12–17 . This has expanded the profession’s scope of practice but resulted in inconsistency as generalist health librarians who perform a range of library duties do not have the same search proficiency.…”
Section: Background To Reviewmentioning
confidence: 99%